2020
DOI: 10.1021/acscatal.0c03686
|View full text |Cite
|
Sign up to set email alerts
|

PdSO4 Surfaces in Methane Oxidation Catalysts: DFT Studies on Stability, Reactivity, and Water Inhibition

Abstract: Although it is experimentally difficult to observe, PdSO4 is considered to be the culprit for the reduced activity of SO2-poisoned methane oxidation catalysts. Density functional theory (DFT) predicts that the formation of bulk PdSO4 is unlikely, which explains the lack of X-ray diffraction (XRD) evidence for the PdSO4 phase. Instead, experimental observations support the idea of PdSO4 being formed on PdO as thin films. Our study found PdSO4(110) and PdSO4(111), corresponding to PdO(100) and PdO(101), respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…[33] Figure 3 shows the results of a light-off experiment in which a Rh/ZSM-5 catalyst achieves a conversion of 50 % at a temperature that is 50 °C less than Pd/ZSM-5 when both water and SO 2 is present, which may be explained by the lower decomposition temperature of RhSO 4 compared to PdSO 4 . Figure 4 shows the DFT model of water adsorbed on the unsaturated Pd atom of a clean PdSO 4 surface proposed by Suvanto et al [62] Based on these results, it appears that the design of catalysts that form unstable sulfates or have hydrophobic environments that keep excess water from the active sites may be a reasonable strategy to achieve a high catalytic activity and stability.…”
Section: Deactivation By So 2 Poisoningmentioning
confidence: 97%
See 3 more Smart Citations
“…[33] Figure 3 shows the results of a light-off experiment in which a Rh/ZSM-5 catalyst achieves a conversion of 50 % at a temperature that is 50 °C less than Pd/ZSM-5 when both water and SO 2 is present, which may be explained by the lower decomposition temperature of RhSO 4 compared to PdSO 4 . Figure 4 shows the DFT model of water adsorbed on the unsaturated Pd atom of a clean PdSO 4 surface proposed by Suvanto et al [62] Based on these results, it appears that the design of catalysts that form unstable sulfates or have hydrophobic environments that keep excess water from the active sites may be a reasonable strategy to achieve a high catalytic activity and stability.…”
Section: Deactivation By So 2 Poisoningmentioning
confidence: 97%
“…RhSO 4 decomposes at a lower temperature than PdSO 4 and therefore remains active in a broader operation range with SO 2 present. [32,61] Suvanto et al [62] recently showed that the deactivation caused by SO 2 poisoning and water are interconnected, emphasizing the importance of having both species present during catalytic testing. The authors used density-functional theory (DFT) calculations to show that the PdSO 4 (111) surface strongly adsorbs water.…”
Section: Deactivation By So 2 Poisoningmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the process of how the products of the chemical reaction are determined is a challenging matter, as the products are considered to be the results of complex behaviors. Methane oxidation is a process where the interaction of methane (CH 4 ) and oxygen (O 2 ) produces carbon dioxide (CO 2 ). Methane oxidation also produces other key molecules such as carbon monooxide (CO), ethylene (C 2 H 4 ), ethane (C 2 H 6 ), and methanol (CH 3 OH) depending on the experimental process conditions as well as the introduction of catalysts; however, it is challenging to precisely identify how these molecules behave during the reaction in experimental characterization. Although microkinetic analysis combined with first-principles calculations gives an atomic-level understanding, the representation of methane oxidation upon a change in experimental conditions is a difficult task .…”
mentioning
confidence: 99%